Comparison of the neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios in normoglycemic and hyperglycemic subjects - Mendes,Brena Barros (2019)
ABSTRACT Objective: To compare the neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios as possible parameters of systemic inflammation in hyperglycemic and normoglycemic subjects. Methods: A retrospective, cross-sectional study of data collected from patients tested for fasting blood glucose, glycated hemoglobin (HbA1c) and blood count on the same day, between July and December 2016. Patients were divided into hyperglycemic and normoglycemic, and matched by age and sex. The data were analyzed using Epi Info™, version 7.2.1.0, for the Windows® platform. Results: We enrolled 278 subjects, 139 hyperglycemic and 139 normoglycemic. The absolute number of leukocytes and neutrophils was higher in the Hyperglycemic Group (p=0.006 and p=0.004, respectively). There was no difference in the neutrophil-to-lymphocyte ratio between the Hyperglycemic Group and the Normoglycemic Group (2.1 versus 2.0; p=0.264), and both neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios showed no differences between those with HbA1c ≥7% (n=127, p=0.778) and those with HbA1c <7% (n=12, p=0.490). In contrast, the platelet-to-lymphocyte ratio was lower in the Hyperglycemic Group (117.8 versus 129.6; p=0.007). Conclusion: Hyperglycemic subjects had a neutrophil-to-lymphocyte ratio similar to that of normoglycemic subjects, but had a lower platelet-to-lymphocyte ratio. Future prospective studies will be useful to determine the importance and prognostic value of neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios in the hyperglycemic state.